PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPA DENGAN MENGGUNAKAN PENDEKATAN KONSTRUKTIVISME - mardiyanti, eva; zen, mulyani; ahmad, syafri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research was to describe the improvement of students’ learning result by using the constructivism approach. This research was a classroom research using qualitative and quantitative approach. The subject of the research were teacher and 25 students. The result in cycle I lesson plane assessment was 77%, teacher’s activity was 73%, student’s activity74%, and the learning result was 46%. It improved in cycle II became 97%, 86%, 93% and 82%. In conclusion, constructivism approach in learning science subject was success to improve the student’s learning result in elementary school. Keywords : study’s result science, constructivism approach